Utilization of Septic Tank Waste to Enhancement the Growth of Spinach in Various Media - Ahmad Arif Darmawan; Akhmad Fatah Hidayat; Adib Aditya Permadi; Hendri Wibowo; Reo Sambodo; A.H. Syaeful Anwar; Joko Maryanto; M. Nazarudin Budiono; Renan Subantoro; Eni Yulianingsih; Ika Ferry Yunianti (Journal of Applied Agricultural Science and Technology, 2023)
Septic tank waste can be used as a new alternative to be used as fertilizer because human excrement contains the availability of nutrients needed by plants. The research aimed to know the effect of liquid organic fertilizers dose, and plant media type of both to increase the growth and the production of plant spinach. The experimental design used was Block Randomized Design factorial with 9 treatments and 3 replicates. The first factor consists of 3 doses of fermented septic tank waste of human feces. Namely doses of 0 mL/plant (K1), 0,4 mL/plant (K2), 0,6 mL/plant (K3). The second factor is the planting medium consisting of 3 kinds of land or control (M0), land + husk charcoal (M1), land + Manure (M2). The observed variables include the number of leaves, plant height, root length, fresh weight of plant, root fresh weight, dry weight, root dry weight of the plant. The results showed that the fermented septic tank waste 0,6 mL (K3) influential real against the number of leaves. Granting planting media differ very markedly against all variable observations i.e. high number of plants, leaves, root length, fresh weight of plant, root fresh weight, dry weight, root dry weight of the plant. All variables are not found the existence of an interaction between fermented septic tank waste with the media.